Development Status and Challenges of Thermal Insulation in Large Liquid Hydrogen Storage Tanks - Yang Haonan; Yin Liang; Ju Yonglin (Zhileng xuebao)
Hydrogen energy, as a carbon-free energy source and a pivotal technology for attaining the goals of "carbon peaking and carbon neutrality", has attracted considerable global interest in recent years. The storage of liquid hydrogen offers several advantages owing to its high hydrogen storage density, low storage pressure, and high energy density. However, the industrial development of hydrogen energy still faces many problems. Technologies for large-scale, long-term storage and long-distance transportation are crucial problems in the utilization of liquid hydrogen. Therefore, it is necessary to develop efficient technologies for storing and transporting liquid hydrogen and to build large liquid hydrogen storage tanks with good thermal insulation performance. In this paper, the development status of large liquid hydrogen storage tank storage technology at home and abroad is reviewed, and key problems such as cryogenic insulation and material thermal stress in liquid hydrogen storage are analyzed. The difficulties associated with hydrogen storage and transportation are highlighted, and the development direction of liquid hydrogen storage technology is examined.